Case Report: Lung Ultrasound in Critically Ill Neonates With Lung Diseases: Experience From Several Typical Cases - Deng, Biying; Xu, Fengdan; Li, Jinfeng; Mai, Minling; Chen, Qin; Liao, Jinfeng; He, Xiaoguang; Li, Ning (Frontiers in Pediatrics, 2022)
Lung ultrasound (LUS) can be used to diagnose various neonatal lung diseases. It more sensitively diagnoses pulmonary edema, pneumothorax, pulmonary consolidation, and atelectasis than traditional X-ray and quickly determines the cause of dyspnea. As a component of severe ultrasound, LUS enables rapid bedside visualization of lung diseases and plays a major role in guiding the differential diagnosis of disease, ventilator treatment, and lung recruitment. This study introduced the application of LUS in the diagnosis and treatment of critically ill neonates with lung diseases.